The NSEAD Survey Report 2015–16: Political Reflections from Two Art and Design Educators. (25th December 2017) - Payne, Rachel; Hall, Emese
Abstract: In 2015 the (UK) National Society for Education in Art and Design (NSEAD) conducted their biggest and most comprehensive survey to date with art and design educators. Some 1, 191 teachers and lecturers employed in early years to further education settings across England and Wales responded to the survey, which aimed to capture how government policy since 2010 has affected art and design education. Four key areas were examined: curriculum provision; value given to the subject within the school community; professional development opportunities; and well‐being and workload. The results are troubling, indicating a systemic marginalisation of art and design across all sectors, evident in a reduction in choice, provision and curriculum time, and evidence of falling standards in student attainment at primary to secondary transfer. We supported the NSEAD with constructing the survey and writing the report and in this article we utilise the Survey Report to fuel a broader discussion about our concerns regarding the demise of art and design education. Value is identified as an essential theme and we posit that our subject, largely due to neoliberalist policy, is currently perceived as a 'bimbo': attractive, but unintelligent and frivolous. In this article we pay particular attention to the value of art and design education from a political perspective, challenging narrow government agendas.